A novel deep earth observation-oriented methods for enhancing magnetometry sensor stability. (30th November 2022) - Yang, Hongfei; Sun, Yongze; Xu, Hongxu; Yao, Zongwei; Wang, Yanzhang
Highlights: A thermal management system has been designed for extreme conditions in deep wells. The system combines an active cooling cycle and passive vacuum isolation. Experiments showed that the system enables sensors to operate stably at a high temperature of 210°C for over 3 months. Abstract: The existing magnetic sensors are sensitive to temperature and are prone to temperature drift, which makes it difficult to guarantee detection accuracy when working continuously at high temperatures downhole for long periods of time. Moreover, the confined space underground greatly affects the installation and working of equipment. To this end, this paper proposes a method to enhance the stability of magnetic measurements in deep wells. Firstly, the fact that the stability of the magnetic sensor is subject to temperature is verified at four temperatures; then, the effect of the proposed method on the stability of the magnetic sensor at four temperatures of 120 °C, 150 °C, 180 °C and 210 °C is demonstrated through simulations and experiments; subsequently, the long-term stability of the method is confirmed by ageing tests in the extreme high temperature environment; finally, field experiments are conducted to reaffirm the effectiveness and engineering feasibility of the method.